E-Learning Using Wordpress on Physics Materials with The 5E Learning Cycle Strategy - Dewi Muliyati; Herga Marizka; Fauzi Bakri (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2019)
This article aims to publish research results in developing e-learning tools using WordPress in high school physics learning with the 5E Learning Cycle strategy. The 5E Learning Cycle Strategy consists of five stages: Engagement, Explore, Explain, Elaborate, and Evaluate. The 5E Learning Cycle Strategy refers to learner-centered learning so that online-based learning media is needed that can condition the implementation of learning following the 5E Learning Cycle stages. This study uses research and development that refers to the Dick and Carey model. E-learning products produce five physics topics, namely 1) Direct Current (DC) Circuit; 2) Static Electricity; 3) Magnetic Field; 4) Electromagnetic Induction; and 5) Alternating Current (AC) Circuit. It was validated by material physic experts, media experts, and learning experts, in the form of a Likert-scale questionnaire. The results of field trials using e-learning products produce N-Gain values ranging from 0.35 to 0.40. The study concluded that the developed e-learning could support physics learning with the Learning Cycle 5E strategy.